Comparison of quantitative gonad maturation scales in a temperate oyster (Crassostrea gigas) and a sub-tropical oyster (Crassostrea corteziensis). Issue 3 (3rd July 2017) - Rodríguez-Jaramillo, C.; Ibarra, A. M.; Soudant, P.; Palacios, E.
Abstract: Quantitative scales to evaluate maturity of female gonads were compared for a temperate oyster, Crassostrea gigas and a tropical oyster, Crassostrea corteziensis grown in the same locality. C. gigas had well-defined maturation and spawning periods and a resting phase in winter; in C. corteziensis mature individuals occurred most of the year and there were several spawning peaks. Of the quantitative scales used here, average oocyte diameter and gonad coverage area, much used for C. gigas, and ovary maturity index, less used, were inadequate to distinguish the reproductive pattern of C. corteziensis, since they both skewed the degree of maturation in vitellogenic stages in favor of C. gigas . Maximum oocyte diameter and maximum cytoplasm area were different among species at vitellogenic stages and also in previtellogenic stages. Nucleus:cytoplasm ratio was significantly different in previtellogenic and spawned stages between C. gigas and C. corteziensis . The Index of gonadal development was skewed in favor of C. gigas in postvitellogenic stage. The only scale that was comparable between species was reproductive potential, but it also was one of the most laborious. Other ordinal scales commonly used, such as a visual external evaluation of the gonad, only classified correctly a quarter of the stages.